2018
DOI: 10.1111/php.12992
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Removal Under Solar Illumination Over Ag3VO4/mpg‐C3N4 Heterojunction Photocatalysts

Abstract: Ag VO /mpg-C N (mesoporous graphitic carbon nitride) heterojunction photocatalysts were prepared by anchoring tiny Ag VO particles on the nanosheet of mpg-C N . The prepared Ag VO /mpg-C N heterojunctions were used to remove tetracycline (TC), a kind of antibiotics widely released into the aquatic environment under solar irradiation. Compared with pure mpg-C N and Ag VO , Ag VO /mpg-C N displayed much higher photocatalytic activity (83.2% removal rate within 90 min under visible-light irradiation). Importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…It can be stated that CdZnS/SnS 2 /SnO 2 will be more efficient than other photocatalysts in transferring the photogenerated carriers to the adsorbed pollutants. The comparison of photoexcited carrier separation and photocatalysts efficiency is widely used to be analyzed by transient photocurrent [46] . The transient photocurrent responses of five samples for ten on‐off cycles are displayed in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be stated that CdZnS/SnS 2 /SnO 2 will be more efficient than other photocatalysts in transferring the photogenerated carriers to the adsorbed pollutants. The comparison of photoexcited carrier separation and photocatalysts efficiency is widely used to be analyzed by transient photocurrent [46] . The transient photocurrent responses of five samples for ten on‐off cycles are displayed in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of photoexcited carrier separation and photocatalysts efficiency is widely used to be analyzed by transient photocurrent. [46] The transient photocurrent responses of five samples for ten on-off cycles are displayed in Figure S5. Compared with the other samples, the CdZnS/SnS 2 /SnO 2 heterostructure has higher transient photocurrent density.…”
Section: Transient Photocurrent Response and Nyquist Plots Analysismentioning
confidence: 99%
“…It is concluded that all tested working electrodes are increased photocurrent responses after irradiation, and the generated photocurrents are stable and reproducible. The Ag/ETS‐10 sample is more stable and exhibited higher photocurrents than the ETS‐10, demonstrating a longer lifetime and more efficient separation of photoinduced e − ‐h + pairs [44] . To study the charge transport properties and interfacial resistance of ETS‐10 and Ag/ETS‐10 samples, the electrochemical impedance (EIS) measurements were used to analyze and the results are shown in Figure 7b.…”
Section: Resultsmentioning
confidence: 99%
“…The Ag/ETS-10 sample is more stable and exhibited higher photocurrents than the ETS-10, demonstrating a longer lifetime and more efficient separation of photoinduced e À -h + pairs. [44] To study the charge transport properties and interfacial resistance of ETS-10 and Ag/ETS-10 samples, the electrochemical impedance (EIS) measurements were used to analyze and the results are shown in Figure 7b. The radius of photocatalyst Ag/ETS-10 is much smaller than that of ETS-10, which further demonstrates that Ag/ETS-10 reduces the recombination probability of e À -h + pairs and promotes the transfer of photo-generated electrons.…”
Section: Photodegradation Mechanismmentioning
confidence: 99%
“…To identify the dominant active species in photocatalysis, the free radical trapping experiments were carried out by adding EDTA-2Na, isopropyl alcohol (IPA), and benzoquinone (BQ) to quench h + , cOH, and cO 2 À , respectively. 53 It can be seen that the photocatalytic activity is restrained on adding the EDTA-2Na, IPA, and BQ scavengers under UV-light irradiation (Fig. S19a †).…”
Section: Congo Red Photocatalytic Degradation and Mechanismmentioning
confidence: 98%